Heat preservation aerogel aramid fiber heat insulation felt and preparation method thereof

By adding 2,3-pyrazine diacid anhydride to the meta-aramidine polymer, and combining talc powder treatment and acupuncture technology, the existing aerogel insulation felt was solved, and high-strength, low-thermal insulation aerogel thermal aerogel thermal aerogel thermal aerogel thermal aerogel is prepared, achieving widespread application in the field of high-temperature fire protection.

CN119877194AActive Publication Date: 2025-04-25TAYHO ADVANCED MATERIALS GRP CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510386543.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-25
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

The existing aerogel insulation felt has powder loss problem and is difficult to apply in the wearable field. The flame retardant effect of conventional insulation felt is poor and cannot be widely used in the field of high-temperature protection.

Method used

By adding 2,3-pyrazine dianhydride to the reaction system of the meta-aramid polymer, meta-aramid aerogel fiber was prepared, and combined with talc powder treatment and acupuncture technology, a high-strength, low-thermal insulation aerogel aramid heat-insulating felt was prepared.

Benefits of technology

The problem of powder loss of aerogel insulation felt is solved, the strength and flame retardant performance of the heat-insulating felt are improved, and the widespread application in the field of high-temperature fire protection is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of thermal insulation materials, in particular to a thermal insulation aerogel aramid fiber thermal insulation felt and a preparation method thereof.The preparation method comprises the steps that 2, 3-pyrazine dianhydride is added into a reaction system for preparing meta-position aramid fiber polymers through polymerization for a reaction, a spinning solution is obtained, fibers are prepared through wet spinning, and the thermal insulation aerogel aramid fiber thermal insulation felt is obtained. Then the fibers are made into meta-position aramid fiber aerogel tows; carrying out cutting treatment on the meta-position aramid fiber aerogel tows to obtain short-cut meta-position aramid fiber aerogel, and then treating the short-cut meta-position aramid fiber aerogel by using talcum powder; processing the chopped meta-position aramid fiber aerogel processed by the talcum powder and the meta-position aramid fiber by using an opening and carding machine together, uniformly mixing, and then performing needling treatment to obtain the heat-preservation aerogel aramid fiber heat-insulation felt. The heat insulation felt has high heat preservation performance and low heat conduction performance, solves the problems of powder falling and the like of composite silicon dioxide of a conventional heat insulation felt, and has good strength performance and flame retardant performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a thermal insulation aerogel aramid insulation felt and a preparation method thereof, belonging to the technical field of thermal insulation materials. Background Art

[0002] Insulation felt is a flexible insulation material made of fiber material through a specific process. It is widely used in industrial equipment, construction, aerospace, automobile and other fields. With the rapid development of technology in various fields, the performance requirements for thermal insulation materials are getting higher and higher.

[0003] Existing aerogel thermal insulation felts are generally in the form of silica composites, which have serious powdering problems and are difficult to be used in the wearable field. For example, the patent application with publication number CN112709075A discloses a high-strength aerogel-modified thermal insulation felt, including an aluminum silicate fiber felt substrate, a polyamide nanofiber / carbon nanotube composite gel coating, and a silicon aerogel-modified fluorocarbon resin coating sequentially arranged on the aluminum silicate fiber felt substrate; in the polyamide nanofiber / carbon nanotube fiber composite gel coating, the silicon aerogel-modified fluorocarbon resin coating includes polymer-modified nano-silica aerogel, fluorocarbon resin, and additives. This method uses the method of silica composite. In addition, conventional thermal insulation felts are PET felt cloths, which have poor flame retardant effects and are difficult to use in high-temperature protection fields such as degreasing furnaces, high-temperature carbonization furnaces, low-temperature carbonization furnaces, CVD furnaces, and CVI furnaces.

[0004] Meta-aramid is a high-performance fiber that is resistant to high temperatures and inherently flame-retardant. It is widely used in aerospace, personal protection, high-temperature filtration and other fields. In the field of new thermal insulation, aramid products have poor thermal insulation effects and cannot be widely used. In addition, during the preparation process of aramid thermal insulation felt, there are also problems such as high static electricity and inability to loosen. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a thermal insulation aerogel aramid insulation felt and a preparation method thereof, which has high thermal insulation and low thermal conductivity, and solves the problems of conventional thermal insulation felt composite silica powder shedding and the like; at the same time, the meta-aramid aerogel felt has an intrinsic flame retardant effect and can be widely used in the field of high temperature resistance and fire prevention. In addition, the preparation method also solves the problem that the meta-aramid aerogel felt cannot be produced continuously due to high static electricity during the preparation process.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a thermal insulation aerogel aramid insulation felt, the preparation method is: S1. Adding 2,3-pyrazine dianhydride to a reaction system for preparing meta-aramid polymer by polymerization to carry out reaction to obtain a spinning solution, preparing fibers by wet spinning, and then making the fibers into meta-aramid aerogel tows; S2, cutting the meta-aramid aerogel tow to obtain short-cut meta-aramid aerogel, and then treating the short-cut meta-aramid aerogel with talcum powder; S3, the talcum powder treated short-cut meta-aramid aerogel and meta-aramid fiber are processed together by using an opening and carding machine to make them evenly mixed, and then the thermal insulation aerogel aramid insulation felt is obtained by needle punching.

[0007] Furthermore, in step S1, 2,3-pyrazine dianhydride is added during the condensation polymerization of m-phenylenediamine and isophthaloyl chloride to prepare a meta-aramid polymer, wherein the amount of 2,3-pyrazine dianhydride added is 0.1-0.5% of the molar number of m-phenylenediamine. After the reaction is completed, the spinning solution is neutralized to obtain a spinning solution, and the viscosity of the spinning solution at 25° C. is 1000-1500 Po.

[0008] Furthermore, two coagulation baths are used in the wet spinning process, the first coagulation bath is a mixed solution of DMAC and water, the mass concentration of DMAC is 10-15%, the length of the first coagulation bath is 0.3-0.5 m, and the temperature is 50-60°C; The second coagulation bath is a mixed solution of DMAC, water and calcium chloride, the mass concentration of calcium chloride is 0.5-2%, the mass concentration of DMAC is 80-85%, the length of the second coagulation bath is 8-10m, and the temperature is 5-10℃.

[0009] Furthermore, the length of the short-cut meta-aramid aerogel is 20-100 mm, and the amount of talcum powder added is 0.5-1 wt % of the mass of the short-cut meta-aramid aerogel.

[0010] Furthermore, the mass ratio of the short-cut meta-aramid aerogel to the meta-aramid fiber is 1:(0.2-0.4).

[0011] Furthermore, in the opening process, short-cut meta-aramid aerogel is first used, and then the meta-aramid fiber is gradually added. The opening speed of the short-cut meta-aramid aerogel is 8-10 m / min, and the opening speed of the meta-aramid fiber is 2-4 m / min; the opening pressure is 0.1-0.5Mpa.

[0012] Furthermore, during the carding process, nitrogen gas is used for purging, with a nitrogen flow rate of 0.2-0.5 m 3 / min.

[0013] Furthermore, in step S3, the ambient humidity is controlled to be 60%-65%, the acupuncture thickness is 3-8 mm, and the acupuncture density is 100-150 needles / cm 2 .

[0014] The invention also discloses a thermal insulation aerogel aramid insulation felt, and the thermal insulation aerogel aramid insulation felt is prepared according to the preparation method of the invention.

[0015] Furthermore, the thermal insulation aerogel aramid insulation felt has a gram weight of 150-200 g / m 2 , thermal conductivity is 0.005-0.015 W / m·K, and the strength of aerogel felt is 110-150MPa.

[0016] The beneficial effects of the present invention are: The thermal insulation felt of the present invention has high thermal insulation and low thermal conductivity, solves the problem of conventional thermal insulation felt composite silica powder falling, and has good strength performance. At the same time, the thermal insulation felt of the present invention has good flame retardant performance and can be widely used in the field of high temperature resistance and fire prevention.

[0017] In the method for preparing the thermal insulation felt of the present invention, by adding 2,3-pyrazine dianhydride during the preparation of the meta-aramid polymer, the strength performance of the meta-aramid aerogel fiber can be improved, which is more conducive to the application in the thermal insulation felt and reduces the damage to the internal pores of the meta-aramid aerogel fiber during the processing and manufacturing of the thermal insulation felt, thereby affecting the thermal insulation performance of the thermal insulation felt; and then a suitable proportion of conventional meta-aramid fibers are added, so that the prepared thermal insulation felt has excellent thermal insulation and flame retardant properties while still maintaining good strength properties.

[0018] In the method for preparing the thermal insulation felt of the present invention, a suitable amount of talcum powder is used to treat the meta-aramid aerogel in cooperation with a suitable environmental humidity, which can solve the problem that the meta-aramid aerogel fiber is affected by the static electricity and thus the smooth processing and preparation of the thermal insulation felt is affected, and at the same time, the problem of powder loss and obvious damage to the strength performance of the thermal insulation felt is avoided, thereby obtaining a thermal insulation felt with better performance.

[0019] In addition, in the method for preparing the thermal insulation felt described in the present invention, by adopting appropriate opening and carding conditions, conventional meta-aramid fibers and short-cut meta-aramid aerogels are evenly distributed, while avoiding damage to the aerogel structure during the preparation process. At the same time, appropriate needling conditions are combined to obtain a high-strength, high-thermal insulation felt. DETAILED DESCRIPTION

[0020] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0022] A method for preparing a thermal insulation aerogel aramid insulation felt, the preparation method comprising: S1. Adding 2,3-pyrazine dianhydride to a reaction system for preparing meta-aramid polymer by polymerization to react to obtain a spinning solution, preparing fibers by wet spinning, and then stretching, washing, curling, and freeze-drying the fibers to prepare meta-aramid aerogel tows; S2, cutting the meta-aramid aerogel tow to obtain short-cut meta-aramid aerogel, and then treating the short-cut meta-aramid aerogel with talcum powder; S3, the talcum powder treated short-cut meta-aramid aerogel and meta-aramid fiber are processed together by using an opening and carding machine to make them evenly mixed, and then the thermal insulation aerogel aramid insulation felt is obtained by needle punching.

[0023] Specifically, in step S1, m-phenylenediamine and 2,3-pyrazine dianhydride are dissolved in a corresponding solvent, and then isophthaloyl chloride is added for condensation polymerization to prepare a meta-aramid polymer, wherein the amount of 2,3-pyrazine dianhydride added is 0.1-0.5% of the molar number of m-phenylenediamine. After the reaction is completed, the spinning solution is neutralized to obtain a spinning solution having a viscosity of 1000-1500 Po at 25°C.

[0024] More specifically, the molar ratio of m-phenylenediamine to isophthaloyl chloride is 1:(0.99-1.00), the solvent used in the condensation polymerization process is DMAC, DMF, DMSO or NMP, and the reaction temperature is 10-20°C; during the neutralization treatment, the neutralizing agent added is calcium hydroxide or sodium hydroxide.

[0025] Specifically, two coagulation baths are used in the wet spinning process, the first coagulation bath is a mixed solution of DMAC and water, the mass concentration of DMAC is 10-15%, the length of the first coagulation bath is 0.3-0.5m, and the temperature is 50-60°C; The second coagulation bath is a mixed solution of DMAC, water and calcium chloride, the mass concentration of calcium chloride is 0.5-2%, the mass concentration of DMAC is 80-85%, the length of the second coagulation bath is 8-10m, and the temperature is 5-10℃.

[0026] The first coagulation bath can make the fiber form a dense skin-core structure so that the fiber can form internal pores. The second coagulation bath can slowly exchange the calcium chloride (chloride salt) inside the fiber with the coagulation bath, so that a complete chloride salt departure channel is formed inside the fiber, ensuring that the fiber forms more dense pores.

[0027] More specifically, in the embodiment of the present invention, the specific conditions for stretching, washing, curling and freeze-drying for preparing the meta-aramid aerogel tow are as follows: the drawing ratio is 1.45-1.50, the washing temperature is 30-35°C, and the freeze-drying adopts a gradient freeze-drying method, that is, freeze-drying at -20°C for 4 hours, freeze-drying at 0°C for 4 hours, and freeze-drying at 10°C for 48 hours to obtain the meta-aramid aerogel tow.

[0028] More specifically, the meta-aramid aerogel tow has a fiber fineness of 1-10 D, and a CV% of the fiber fineness ≤5%.

[0029] Specifically, the length of the short-cut meta-aramid aerogel is 20-100 mm, and the added amount of the talc is 0.5-1 wt % of the mass of the short-cut meta-aramid aerogel.

[0030] More specifically, the talc is conventional nano-grade talc or silane-modified talc.

[0031] More preferably, the talc is silane-modified talc, specifically nano-scale talc with a particle size of less than 1 μm. The silane-modified talc is prepared in-house, and the specific preparation method is as follows: calcining the talc (300°C) to remove water; dissolving the silane coupling agent (KH-550) in an ethanol / water mixed solvent (weight ratio of 1:1) to obtain a silane solution; then adding the calcined talc to the silane solution, stirring and reacting at 80°C for 2 hours, wherein the silane coupling agent is 3% of the mass of the talc. After the reaction is completed, centrifugation and drying are performed to obtain the silane-modified talc.

[0032] The use of silane-modified talc is more conducive to uniform dispersion in short-cut meta-aramid aerogel, and has a high degree of bonding with meta-aramid, which is helpful in solving the problem of high static electricity and inability to produce continuously during the production of thermal insulation felt.

[0033] Specifically, the mass ratio of the chopped meta-aramid aerogel to the meta-aramid fiber (Temida N602) is 1:(0.2-0.4).

[0034] Specifically, in the opening process, short-cut meta-aramid aerogel is first used, and then the meta-aramid fiber is gradually added. The opening speed of the short-cut meta-aramid aerogel is 8-10 m / min, and the opening speed of the meta-aramid fiber is 2-4 m / min; the opening pressure is 0.1-0.5 Mpa.

[0035] Specifically, during the carding process, nitrogen is used for purging, and the nitrogen flow rate is 0.2-0.5 m 3 / min.

[0036] Specifically, in step S3, the ambient humidity is controlled to be 60%-65%, the acupuncture thickness is 3-8 mm, and the acupuncture density is 100-150 needles / cm2 Under the conditions of needle punching thickness and needle punching density, the damage to the pore structure of the meta-aramid aerogel can be reduced, and the strength reduction problem of the thermal insulation felt caused by the high flexibility of the meta-aramid aerogel can be reduced, thereby obtaining a thermal insulation felt with high strength and high thermal insulation performance.

[0037] A thermal insulation aerogel aramid insulation felt is prepared according to the preparation method of the present invention.

[0038] Specifically, the thermal insulation aerogel aramid insulation felt has a gram weight of 150-200 g / m 2 , thermal conductivity is 0.005-0.015W / m·K, and the strength of aerogel felt is 110-150MPa.

[0039] Example 1 S1, m-phenylenediamine, isophthaloyl chloride and 2,3-pyrazine dianhydride are polymerized in DMAC, wherein the molar ratio of m-phenylenediamine to isophthaloyl chloride is 1:0.99, and the amount of 2,3-pyrazine dianhydride added is 0.3% of the molar number of the m-phenylenediamine. After the reaction is completed, sodium hydroxide is added for neutralization to obtain a spinning solution, and the viscosity of the spinning solution is 1052Po. Fibers are prepared by wet spinning, and then the fibers are stretched, washed, curled, and freeze-dried to obtain the meta-aramid aerogel tow; Among them, two coagulation baths are used in the wet spinning process. The first coagulation bath is a mixed solution of DMAC and water, the mass concentration of DMAC is 10%, the length of the first coagulation bath is 0.3m, and the temperature is 50°C; The second coagulation bath was a mixed solution of DMAC, water and calcium chloride, with a calcium chloride mass concentration of 0.5% and a DMAC mass concentration of 80%. The second coagulation bath had a length of 8 m and a temperature of 5°C.

[0040] S2. Cutting the meta-aramid aerogel tow to obtain short-cut meta-aramid aerogel, and then treating the short-cut meta-aramid aerogel with talcum powder; the talcum powder is conventional nano-grade talcum powder, and the amount of talcum powder added is 0.5wt% of the mass of the short-cut meta-aramid aerogel.

[0041] S3, treating the talcum powder treated short-cut meta-aramid aerogel and meta-aramid fiber together using an opening and carding machine to make them evenly mixed, and then subjecting them to a needle punching treatment to obtain the thermal insulation aerogel aramid insulation felt; The mass ratio of short-cut meta-aramid aerogel to meta-aramid fiber is 1:0.2. In the opening process, short-cut meta-aramid aerogel is used first, and then the meta-aramid fiber is gradually added. The opening speed of the short-cut meta-aramid aerogel is 10 m / min, and the opening speed of the meta-aramid fiber is 4 m / min. The opening pressure is 0.1 Mpa. During the carding process, nitrogen is used for purging, and the nitrogen flow rate is 0.2 m 3 / min; the ambient humidity was controlled at 60%, the acupuncture thickness was 3mm, and the acupuncture density was 150 needles / cm 2 .

[0042] Example 2 S1, m-phenylenediamine, isophthaloyl chloride and 2,3-pyrazine dianhydride are polymerized in DMF, wherein the molar ratio of m-phenylenediamine to isophthaloyl chloride is 1:0.992, and the amount of 2,3-pyrazine dianhydride added is 0.1% of the molar number of the m-phenylenediamine. After the reaction is completed, sodium hydroxide is added for neutralization to obtain a spinning solution, and the viscosity of the spinning solution is 1132Po. Fibers are prepared by wet spinning, and then the fibers are stretched, washed, curled, and freeze-dried to obtain the meta-aramid aerogel tow; Among them, two coagulation baths were used in the wet spinning process. The first coagulation bath was a mixed solution of DMAC and water, with a DMAC mass concentration of 11%, a length of 0.35 m, and a temperature of 53 °C. The second coagulation bath was a mixed solution of DMAC, water and calcium chloride, with a calcium chloride mass concentration of 1.0% and a DMAC mass concentration of 81%. The second coagulation bath had a length of 8.5 m and a temperature of 6°C.

[0043] S2. Cutting the meta-aramid aerogel tow to obtain short-cut meta-aramid aerogel, and then treating the short-cut meta-aramid aerogel with talcum powder; the talcum powder is conventional nano-grade talcum powder, and the amount of talcum powder added is 1wt% of the mass of the short-cut meta-aramid aerogel.

[0044] S3, treating the talcum powder treated short-cut meta-aramid aerogel and meta-aramid fiber together using an opening and carding machine to make them evenly mixed, and then subjecting them to a needle punching treatment to obtain the thermal insulation aerogel aramid insulation felt; The mass ratio of short-cut meta-aramid aerogel to meta-aramid fiber is 1:0.25. In the opening process, short-cut meta-aramid aerogel is used first, and then the meta-aramid fiber is gradually added. The opening speed of the short-cut meta-aramid aerogel is 8 m / min, and the opening speed of the meta-aramid fiber is 2 m / min. The opening pressure is 0.2 Mpa. During the carding process, nitrogen is used for purging, and the nitrogen flow rate is 0.5 m 3 / min; the ambient humidity was controlled at 61%, the needle thickness was 5mm, and the needle density was 130 needles / cm 2 .

[0045] Example 3 S1, m-phenylenediamine, isophthaloyl chloride and 2,3-pyrazine dianhydride are polymerized in DMSO, wherein the molar ratio of m-phenylenediamine to isophthaloyl chloride is 1:0.994, and the amount of 2,3-pyrazine dianhydride added is 0.5% of the molar number of m-phenylenediamine. After the reaction is completed, sodium hydroxide is added for neutralization to obtain a spinning solution, and the viscosity of the spinning solution is 1465 Po. Fibers are prepared by wet spinning, and then the fibers are stretched, washed, curled, and freeze-dried to obtain the meta-aramid aerogel tow; Among them, two coagulation baths are used in the wet spinning process. The first coagulation bath is a mixed solution of DMAC and water, the mass concentration of DMAC is 12%, the length of the first coagulation bath is 0.4m, and the temperature is 535℃; The second coagulation bath was a mixed solution of DMAC, water and calcium chloride, with a calcium chloride mass concentration of 1.5% and a DMAC mass concentration of 82%. The second coagulation bath had a length of 9.5 m and a temperature of 8°C.

[0046] S2. Cutting the meta-aramid aerogel tow to obtain short-cut meta-aramid aerogel, and then treating the short-cut meta-aramid aerogel with talcum powder; the talcum powder is conventional nano-grade talcum powder, and the amount of talcum powder added is 0.8wt% of the mass of the short-cut meta-aramid aerogel.

[0047] S3, treating the talcum powder treated short-cut meta-aramid aerogel and meta-aramid fiber together using an opening and carding machine to make them evenly mixed, and then subjecting them to a needle punching treatment to obtain the thermal insulation aerogel aramid insulation felt; The mass ratio of short-cut meta-aramid aerogel to meta-aramid fiber is 1:0.3. In the opening process, short-cut meta-aramid aerogel is used first, and then the meta-aramid fiber is gradually added. The opening speed of the short-cut meta-aramid aerogel is 9 m / min, and the opening speed of the meta-aramid fiber is 3 m / min. The opening pressure is 0.3 Mpa. During the carding process, nitrogen is used for purging, and the nitrogen flow rate is 0.3 m 3 / min; the ambient humidity was controlled at 62%, the acupuncture thickness was 7mm, and the acupuncture density was 120 needles / cm 2 .

[0048] Example 4 S1, m-phenylenediamine, isophthaloyl chloride and 2,3-pyrazine dianhydride are polymerized in DMF, wherein the molar ratio of m-phenylenediamine to isophthaloyl chloride is 1:0.996, and the amount of 2,3-pyrazine dianhydride added is 0.2% of the molar number of m-phenylenediamine. After the reaction is completed, sodium hydroxide is added for neutralization to obtain a spinning solution, and the viscosity of the spinning solution is 1311Po. Fibers are prepared by wet spinning, and then the fibers are stretched, washed, curled, and freeze-dried to obtain the meta-aramid aerogel tow; Among them, two coagulation baths were used in the wet spinning process. The first coagulation bath was a mixed solution of DMAC and water, with a DMAC mass concentration of 13%. The length of the first coagulation bath was 0.45 m and the temperature was 57 °C. The second coagulation bath was a mixed solution of DMAC, water and calcium chloride, with a calcium chloride mass concentration of 1.8% and a DMAC mass concentration of 84%. The second coagulation bath had a length of 9 m and a temperature of 9°C.

[0049] S2. Cutting the meta-aramid aerogel tow to obtain short-cut meta-aramid aerogel, and then treating the short-cut meta-aramid aerogel with talcum powder; the talcum powder is conventional nano-grade talcum powder, and the amount of talcum powder added is 0.7wt% of the mass of the short-cut meta-aramid aerogel.

[0050] S3, treating the talcum powder treated short-cut meta-aramid aerogel and meta-aramid fiber together using an opening and carding machine to make them evenly mixed, and then subjecting them to a needle punching treatment to obtain the thermal insulation aerogel aramid insulation felt; The mass ratio of short-cut meta-aramid aerogel to meta-aramid fiber is 1:0.35. In the opening process, short-cut meta-aramid aerogel is used first, and then the meta-aramid fiber is gradually added. The opening speed of the short-cut meta-aramid aerogel is 10 m / min, and the opening speed of the meta-aramid fiber is 4 m / min. The opening pressure is 0.4 Mpa. During the carding process, nitrogen is used for purging, and the nitrogen flow rate is 0.5 m 3 / min; the ambient humidity was controlled at 63%, the needle thickness was 9mm, and the needle density was 110 needles / cm 2 .

[0051] Example 5 S1, m-phenylenediamine, isophthaloyl chloride and 2,3-pyrazine dianhydride are polymerized in DMAC, wherein the molar ratio of m-phenylenediamine to isophthaloyl chloride is 1:0.998, and the amount of 2,3-pyrazine dianhydride added is 0.4% of the molar number of m-phenylenediamine. After the reaction is completed, sodium hydroxide is added for neutralization to obtain a spinning solution, and the viscosity of the spinning solution is 1285 Po. Fibers are prepared by wet spinning, and then the fibers are stretched, washed, curled, and freeze-dried to obtain the meta-aramid aerogel tow; Among them, two coagulation baths are used in the wet spinning process. The first coagulation bath is a mixed solution of DMAC and water, the mass concentration of DMAC is 15%, the length of the first coagulation bath is 0.5m, and the temperature is 60°C; The second coagulation bath was a mixed solution of DMAC, water and calcium chloride, with a calcium chloride mass concentration of 2% and a DMAC mass concentration of 85%. The second coagulation bath had a length of 10 m and a temperature of 10°C.

[0052] S2. Cutting the meta-aramid aerogel tow to obtain short-cut meta-aramid aerogel, and then treating the short-cut meta-aramid aerogel with talcum powder; the talcum powder is conventional nano-grade talcum powder, and the amount of talcum powder added is 0.6wt% of the mass of the short-cut meta-aramid aerogel.

[0053] S3, treating the talcum powder treated short-cut meta-aramid aerogel and meta-aramid fiber together using an opening and carding machine to make them evenly mixed, and then subjecting them to a needle punching treatment to obtain the thermal insulation aerogel aramid insulation felt; The mass ratio of short-cut meta-aramid aerogel to meta-aramid fiber is 1:0.4. In the opening process, short-cut meta-aramid aerogel is used first, and then the meta-aramid fiber is gradually added. The opening speed of the short-cut meta-aramid aerogel is 10 m / min, and the opening speed of the meta-aramid fiber is 4 m / min. The opening pressure is 0.5 Mpa. During the carding process, nitrogen is used for purging, and the nitrogen flow rate is 0.5 m 3 / min; the ambient humidity was controlled at 65%, the acupuncture thickness was 10mm, and the acupuncture density was 100 needles / cm 2 .

[0054] Example 6 S1, m-phenylenediamine, isophthaloyl chloride and 2,3-pyrazine dianhydride are polymerized in DMAC, wherein the molar ratio of m-phenylenediamine to isophthaloyl chloride is 1:0.99, and the amount of 2,3-pyrazine dianhydride added is 0.3% of the molar number of the m-phenylenediamine. After the reaction is completed, sodium hydroxide is added for neutralization to obtain a spinning solution, and the viscosity of the spinning solution is 1052Po. Fibers are prepared by wet spinning, and then the fibers are stretched, washed, curled, and freeze-dried to obtain the meta-aramid aerogel tow; Among them, two coagulation baths are used in the wet spinning process. The first coagulation bath is a mixed solution of DMAC and water, the mass concentration of DMAC is 10%, the length of the first coagulation bath is 0.3m, and the temperature is 50°C; The second coagulation bath was a mixed solution of DMAC, water and calcium chloride, with a calcium chloride mass concentration of 0.5% and a DMAC mass concentration of 80%. The second coagulation bath had a length of 8 m and a temperature of 5°C.

[0055] S2. Cutting the meta-aramid aerogel tow to obtain short-cut meta-aramid aerogel, and then treating the short-cut meta-aramid aerogel with talcum powder; the talcum powder is silane-modified talcum powder, and the amount of talcum powder added is 0.5wt% of the mass of the short-cut meta-aramid aerogel.

[0056] S3, treating the talcum powder treated short-cut meta-aramid aerogel and meta-aramid fiber together using an opening and carding machine to make them evenly mixed, and then subjecting them to a needle punching treatment to obtain the thermal insulation aerogel aramid insulation felt; The mass ratio of short-cut meta-aramid aerogel to meta-aramid fiber is 1:0.2. In the opening process, short-cut meta-aramid aerogel is used first, and then the meta-aramid fiber is gradually added. The opening speed of the short-cut meta-aramid aerogel is 10 m / min, and the opening speed of the meta-aramid fiber is 4 m / min. The opening pressure is 0.1 Mpa. During the carding process, nitrogen is used for purging, and the nitrogen flow rate is 0.2 m 3 / min; the ambient humidity was controlled at 60%, the acupuncture thickness was 3mm, and the acupuncture density was 150 needles / cm 2 .

[0057] Comparative Example 1 The thermal insulation felt was prepared by the same method as in Example 1, except that: in step S1 of this comparative example 1, no 2,3-pyrazine dianhydride was added.

[0058] Comparative Example 2 The spinning solution was prepared by the same method as in Example 1, except that the amount of 2,3-pyrazine dianhydride was increased in Comparative Example 2, and the amount of 2,3-pyrazine dianhydride added in Comparative Example 2 was 1% of the molar number of the m-phenylenediamine. During the preparation process, it was found that severe implosion occurred in the system, and a spinning solution suitable for the spinning process could not be prepared.

[0059] Comparative Example 3 The thermal insulation felt is prepared by the same method as in Example 1, except that: in step S1 of this comparative example 3, only one coagulation bath treatment is used during the wet spinning process, and the first coagulation bath is not performed in this comparative example 3, and only the second coagulation bath is performed.

[0060] Comparative Example 4 The thermal insulation felt was prepared by the same method as in Example 1, except that: in step S2 of this comparative example 4, talcum powder was not used to treat the short-cut meta-aramid aerogel. During the opening and carding process, the electrostatic effect of the short-cut meta-aramid aerogel was relatively strong, and the thermal insulation felt could not be prepared smoothly.

[0061] Comparative Example 5 The thermal insulation felt was prepared by the same method as in Example 1, except that the amount of talcum powder was increased in Comparative Example 5, and the amount of talcum powder added in Comparative Example 5 was 1.5 wt % of the mass of the chopped meta-aramid aerogel.

[0062] Comparative Example 6 The thermal insulation felt was prepared by the same method as in Example 1, except that in step S3 of this comparative example 6, nitrogen purging was not performed during the carding process.

[0063] Comparative Example 7 The thermal insulation felt was prepared by the same method as in Example 1, except that in step S3 of this comparative example 7, the short-cut meta-aramid aerogel and the meta-aramid fiber were mixed to form mixed fibers, and then the mixed fibers were opened together at a rate of 10 m / min.

[0064] Comparative Example 8 The thermal insulation felt was prepared by the same method as in Example 1, except that in step S3 of this comparative example 8, the opening speed of the chopped meta-aramid aerogel was increased, and the opening speed of the chopped meta-aramid aerogel in this comparative example 8 was 12 m / min.

[0065] Comparative Example 9 The thermal insulation felt was prepared by the same method as in Example 1, except that: in step S4 of this comparative example 9, the needle-punched thickness was increased, and the needle-punched thickness of this comparative example 9 was 10 mm.

[0066] The thermal insulation felts prepared in the above embodiments and comparative examples were subjected to performance tests. The specific test results are shown in Table 1 below. The test methods involved are: thermal conductivity test is conducted in accordance with GB / T 11048-2008, and limiting oxygen index test is conducted in accordance with GB5454-85.

[0067] Table 1 Test results of thermal insulation felt performance

[0068] From the above table data, it can be seen that the thermal insulation felts prepared by the preparation method of the present invention in Examples 1 to 6 have excellent thermal insulation performance and strength performance, as well as excellent flame retardancy, and can be used in some high-temperature environment fields. Moreover, all materials are meta-aramid, which is more conducive to subsequent recycling and reuse. In addition, from the comparison of the data of Example 1 and Example 6, it can be seen that when silane-modified talc is used, it is more conducive to maintaining the thermal insulation performance and strength performance of the thermal insulation felt.

[0069] From the comparison of the data of Comparative Example 1 and Example 1, it can be seen that if 2,3-pyrazine dianhydride is not added in step S1, the strength performance of the thermal insulation felt will be reduced. When 2,3-pyrazine dianhydride is added during the polymerization process, the amine group and the acid anhydride can react with a ring-opening reaction, and the pyrazine reacts with the acyl chloride to form a cross-linked structure, thereby improving the strength of the meta-aramid aerogel fiber bundle, which is beneficial for making the thermal insulation felt have good strength. In addition, the high strength of the meta-aramid aerogel fiber bundle can also reduce the damage to the aerogel structure during the processing of the thermal insulation felt, thereby obtaining a thermal insulation felt with relatively excellent strength and thermal insulation properties.

[0070] It can be seen from the data of Comparative Example 2 that if too much 2,3-pyrazine dianhydride is added, it will cause implosion. Therefore, the use of the amount of 2,3-pyrazine dianhydride specified in the present invention is more conducive to the smooth production of high-quality meta-aramid aerogel.

[0071] From the comparison of the data of Comparative Example 3 and Example 1, it can be seen that: if only one period of coagulation bath treatment is performed during the processing of the meta-aramid aerogel fiber bundle, the strength performance of the meta-aramid aerogel fiber bundle will be greatly reduced, which will eventually lead to a decrease in the strength performance of the thermal insulation felt. In addition, due to the low strength of the meta-aramid aerogel fiber bundle, the pore structure of the aerogel is easily damaged during the processing of the thermal insulation felt, which also leads to a decrease in the thermal insulation effect of the thermal insulation felt.

[0072] From the comparison of the data of Comparative Example 4 and Example 1, it can be seen that if talcum powder is not used for treatment in step S2, the electrostatic effect of the meta-aramid fiber is very large and the processing of the thermal insulation felt cannot be realized.

[0073] From the comparison of the data of Comparative Example 5 and Example 1, it can be seen that if the amount of talc used in step S2 is too much, the talc is easy to agglomerate in the chopped meta-aramid aerogel, causing the thermal insulation felt to lose powder, which affects the overall product quality of the thermal insulation felt.

[0074] From the comparison of the data of Comparative Example 6 and Example 1, it can be seen that if nitrogen purging is not performed during the carding process, it is not conducive to uniform bonding between the short-cut meta-aramid aerogel and the meta-aramid fiber, which ultimately affects the comprehensive performance of the thermal insulation felt.

[0075] From the comparison of the data of Comparative Example 7 and Example 1, it can be seen that if the short-cut meta-aramid aerogel and the meta-aramid fiber are mixed in step S3 to form a mixed fiber and then directly opened, the short-cut meta-aramid aerogel and the meta-aramid fiber will not be conducive to uniform bonding, which will eventually affect the comprehensive performance of the thermal insulation felt.

[0076] From the data comparison of Comparative Example 8 and Example 1, it can be seen that if the opening speed of the short-cut meta-aramid aerogel is increased, the thermal insulation performance of the thermal insulation felt decreases, because the inappropriate opening speed will cause the aerogel structure of the short-cut meta-aramid aerogel to be damaged during the opening process, and it is not conducive to the uniform combination of the short-cut meta-aramid aerogel and the meta-aramid fiber. Therefore, the opening conditions defined in the present invention are more conducive to obtaining a thermal insulation felt product with excellent comprehensive performance.

[0077] From the data comparison between Comparative Example 9 and Example 1, it can be seen that if the needle-punched thickness is increased in step S4, the thermal insulation performance of the thermal insulation felt decreases, because the increase in the needle-punched thickness is likely to affect the pore structure of the aerogel, ultimately leading to a decrease in thermal insulation performance.

[0078] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0079] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a thermal insulation aerogel aramid insulation felt, characterized in that: The preparation method is: S1. Adding 2,3-pyrazine dianhydride to a reaction system for preparing meta-aramid polymer by polymerization to carry out reaction to obtain a spinning solution, preparing fibers by wet spinning, and then making the fibers into meta-aramid aerogel tows; S2, cutting the meta-aramid aerogel tow to obtain short-cut meta-aramid aerogel, and then treating the short-cut meta-aramid aerogel with talcum powder; S3, the talcum powder treated short-cut meta-aramid aerogel and meta-aramid fiber are processed together by using an opening and carding machine to make them evenly mixed, and then the thermal insulation aerogel aramid insulation felt is obtained by needle punching.

2. The method for preparing the thermal insulation aerogel aramid insulation felt according to claim 1, characterized in that: In step S1, 2,3-pyrazine dianhydride is added during the condensation polymerization of m-phenylenediamine and isophthaloyl chloride to prepare a meta-aramid polymer, wherein the amount of 2,3-pyrazine dianhydride added is 0.1-0.5% of the molar number of m-phenylenediamine. After the reaction is completed, the spinning solution is neutralized to obtain a spinning solution, and the viscosity of the spinning solution at 25° C. is 1000-1500 Po.

3. The method for preparing the thermal insulation aerogel aramid insulation felt according to claim 1, characterized in that: Two coagulation baths are used in the wet spinning process. The first coagulation bath is a mixed solution of DMAC and water, with a DMAC mass concentration of 10-15%. The length of the first coagulation bath is 0.3-0.5 m, and the temperature is 50-60°C. The second coagulation bath is a mixed solution of DMAC, water and calcium chloride, the mass concentration of calcium chloride is 0.5-2%, the mass concentration of DMAC is 80-85%, the length of the second coagulation bath is 8-10m, and the temperature is 5-10℃.

4. The method for preparing the thermal insulation aerogel aramid insulation felt according to claim 1, characterized in that: The length of the short-cut meta-aramid aerogel is 20-100 mm, and the amount of talc added is 0.5-1 wt % of the mass of the short-cut meta-aramid aerogel.

5. The method for preparing the thermal insulation aerogel aramid insulation felt according to claim 1, characterized in that: The mass ratio of the short-cut meta-aramid aerogel to the meta-aramid fiber is 1:(0.2-0.4).

6. The method for preparing the thermal insulation aerogel aramid insulation felt according to claim 1, characterized in that: In the opening process, short-cut meta-aramid aerogel is first used, and then the meta-aramid fiber is gradually added. The opening speed of the short-cut meta-aramid aerogel is 8-10 m / min, and the opening speed of the meta-aramid fiber is 2-4 m / min; the opening pressure is 0.1-0.5Mpa.

7. The method for preparing the thermal insulation aerogel aramid insulation felt according to claim 1, characterized in that: During the carding process, nitrogen is used for purging, with a nitrogen flow rate of 0.2-0.5 m 3 / min.

8. The method for preparing the thermal insulation aerogel aramid insulation felt according to claim 1, characterized in that: In step S3, the ambient humidity is controlled to be 60%-65%, the acupuncture thickness is 3-8 mm, and the acupuncture density is 100-150 needles / cm 2 .

9. A thermal insulation aerogel aramid insulation felt, characterized in that: The thermal insulation aerogel aramid insulation felt is prepared according to the preparation method according to any one of claims 1-8.

10. The thermal insulation aerogel aramid insulation felt according to claim 9, characterized in that: The thermal insulation aerogel aramid insulation felt has a gram weight of 150-200 g / m 2 , thermal conductivity is 0.005-0.015 W / m·K, and the strength of aerogel felt is 110-150 MPa.

Citation Information

Patent Citations

  • High-strength aerogel modified heat insulation felt and preparation method thereof

    CN112709075A

  • High-temperature polymer aerogel composites

    CN112955313A

  • Aerogel felt and preparation method thereof

    CN117230571A

  • Method for macro spinning of aramid nanofiber

    CN118390197A

  • Aerogel fiber

    EP4407080A2